Sensational Cities - John J. Curley (British Art Studies, 2016)
The controversial and hugely popular exhibition Sensation: Young British Artists from the Saatchi Collection opened at the Royal Academy in London in 1997, before travelling to Berlin and Brooklyn over the next three years. While best remembered for its highly controversial works and brash assertions of “Britishness”, the exhibition, especially its sculptural objects by Damien Hirist and Rachel Whiteread, registers a common, post-industrial attitude to urban space at the end of the millennium. While Sensation might have seemed subversive, it aligns with the rapid gentrification that transformed the former functionality of its host cities into qualities to be fetishized.